2015
DOI: 10.1021/acs.jpcb.5b01840
|View full text |Cite
|
Sign up to set email alerts
|

Free Energy Surface of the Michaelis Complex of Lactate Dehydrogenase: A Network Analysis of Microsecond Simulations

Abstract: It has long been recognized that the structure of a protein creates a hierarchy of conformations interconverting on multiple time scales. The conformational heterogeneity of the Michaelis complex is of particular interest in the context of enzymatic catalysis in which the reactant is usually represented by a single conformation of the enzyme/substrate complex. Lactate dehydrogenase (LDH) catalyzes the interconversion of pyruvate and lactate with concomitant interconversion of two forms of the cofactor nicotina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 24 publications
1
21
2
Order By: Relevance
“…Recently, we estimated the free energy surface of the Michaelis complex of LDH using the cut-based free energy profile (FEP) method. 22 Even though different substrate binding modes were resolved, the basins on the FEP and the substates resolved by vibrational spectroscopy were only compared indirectly through hydrogen bond analysis. Due to the limitation of the method, the relaxation time scales of the system were underestimated by about 4 orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we estimated the free energy surface of the Michaelis complex of LDH using the cut-based free energy profile (FEP) method. 22 Even though different substrate binding modes were resolved, the basins on the FEP and the substates resolved by vibrational spectroscopy were only compared indirectly through hydrogen bond analysis. Due to the limitation of the method, the relaxation time scales of the system were underestimated by about 4 orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…Their mutant is expected to lower the free energy barrier of the reaction, hence exhibits higher acceleration rate compared to the natural enzyme 139. Focusing on correlated motions with the active site loop, Pan and Schwartz explained how the strong conformational heterogeneity may open alternative mechanisms for the chemical step that need to be accounted for when designing de novo enzymes 137. They extended their analysis to designed Kemp Eliminases and their improved variants under LDE, for which they found that LDE selected mutations favor a more dynamic active site that makes use of the donoracceptor compression 140.…”
mentioning
confidence: 99%
“…But due to its weaker interaction, the contribution would be less important. Recently, molecular dynamics study on pyruvate ternary complex also suggested that the hydrogen bonds between these residues and pyruvate form in the encounter complex . Following structural rearrangements and the loop closure, the active site becomes tighter and hydrogen bonding, electrostatic interactions and the hydrophobic effect all come to be stronger.…”
Section: Resultsmentioning
confidence: 99%